Prevelance And Risk Factors for Hepatitis C Virus Infection in Hemodialysis Patients - Rasool, Rounaq; Bhatnagar, Ritu (Journal of Neonatal Surgery, 2025)
Background: Hepatitis C virus (HCV) infections continue to remain a significant global health challenge due to its morbidity and mortality profile. Among individuals undergoing hemodialysis (HD), the incidence of HCV transmission is notably higher than in the general population. Aim: this study aimed to estimate the Seroprevalence of HCV infection and associated risk factors among patients undergoing hemodialysis in a tertiary care hospital. Materials and Methods: This cross-sectional observational study included 300 patients’ undergoing maintenance HD due to chronic kidney disease (CKD). Data collection involved demographic details, frequency of blood transfusion, duration of dialysis, duration of CKD, associated comorbidities, and other risk factors. All enrolled patients were screened for anti-HCV antibodies using an enzyme-linked immunosorbent assay (ELISA). Results: The prevalence of HCV was 13% among hemodialysis patients. The frequency of blood transfusion, duration of CKD, duration of hemodialysis, and not applied infection control measures were found to be significant risk factors for seroconversion. Family history of HCV infection, surgical procedures during the dialysis period, past history of surgery, temporary vascular Access, and HbsAg status were insignificant risk factors for HCV seroconversion. Conclusion: Frequent blood transfusion, longer duration of CKD, longer duration of hemodialysis and failure to applied infection control measures were significant risk factors for HCV seroconversion in dialysis patients